“The work changes my world”: a survey on the experiences of the unemployed people with disabilities over 40 in Lombardy - Zappella, Emanuela (Formazione & insegnamento, 2015)
According to the literature, people over the age of 40 are at risk of being excluded from the labour market. The situation of those who are in possession of a disability certificate is particularly critical: they could (should be able to?) take advantage of their right to be employed within organizations, but find themselves without a job. Through in-depth interviews we collected the experiences of twenty disabled workers who had been unemployed for at least two years, and went to the Bergamo employment center to renew their enrollment on the unemployment register. The interviews were analyzed using a phenomenological approach and the results show that this experience has four key aspects: personal identity, the desire e to be more useful to the company, personal and family balance, and lack of faith in the future.